2019
DOI: 10.1073/pnas.1903374116
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical formation of a strongly correlated dark condensate of dipolar excitons

Abstract: The formation of a dense Bose-Einstein condensate in dark spin states of two-dimensional dipolar excitons is shown to be driven by a dynamical transition to the long-lived dark states. The condensate is stabilized by strong dipole-dipole interactions up to densities high enough for a dark quantum liquid to form. The persistence of dark condensation was observed in recent experiments. A model describing the non-equilibrium dynamics of externally driven coupled dark and bright condensates reproduces the step-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 38 publications
1
11
0
Order By: Relevance
“…Recent experiments have reported that dipolar excitons can realize a two-dimensional quantum gas [7,8] for which quasilong-range coherence [9,10], quantized vortices [10,11] have been reported in GaAs bilayers. The excitons' quasicondensation must then occur following the Berezinskii-Kosterlitz-Thouless (BKT) mechanism [12,13], since for this reduced dimensionality interactions prevent Bose-Einstein condensation with true long-range order, at any finite temperature [14].…”
mentioning
confidence: 99%
“…Recent experiments have reported that dipolar excitons can realize a two-dimensional quantum gas [7,8] for which quasilong-range coherence [9,10], quantized vortices [10,11] have been reported in GaAs bilayers. The excitons' quasicondensation must then occur following the Berezinskii-Kosterlitz-Thouless (BKT) mechanism [12,13], since for this reduced dimensionality interactions prevent Bose-Einstein condensation with true long-range order, at any finite temperature [14].…”
mentioning
confidence: 99%
“…The bosonic description is justified in the dilute limit, where the spatial extent of the electron-hole bound state is significantly smaller than the inter-IX separation. Consequently, the effect of electronic exchange can be safely neglected [36]. The resulting model Hamiltonian comprises a sum over the kinetic energy term in each layer (inter-layer hopping is disallowed) and intra-and inter-layer dipolar interactions.…”
Section: Effective Model and Phase Diagrammentioning
confidence: 99%
“…More concretely, electrically induced IXs in twodimensional DQW structures, either GaAs-or TMDbased, have recently attracted a great deal of interest as a promising platform for observing collective phenomena of interacting quantum dipolar liquids [25,[29][30][31][32][33][34][35][36][37][38][39][40]. Considering multilayered DQW heterostructures is a particularly interesting research avenue, as it enables revealing the anisotropic and attractive component of dipolar interactions, beyond the purely repulsive dipolar interaction within a monolayer.…”
Section: Introductionmentioning
confidence: 99%
“…In bulk materials the concept of exciton condensation is partly ambiguous since the ordered states are difficult to distinguish from density-wave or nematic states 27 . Although exciton condensates were predicted theoretically more than 50 years ago, their experimental identification in bulk materials has suffered as a consequence, although progress has been achieved recently [28][29][30][31] . Experimental advances with two-dimensional materials have solved the ambigu-ity problem by making it possible to prepare devices with strong interactions between subsystems located in different layers that separately have nearly perfectly conserved particle number Interlayer exciton condensation breaks the independent gauge invariance of the individual layers, i.e.…”
Section: Introductionmentioning
confidence: 99%